The man who fell from the sky [large type] - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery., 2016)
"When Robert Walking Bear's body is found in the Wind River mountains, his death appears to be accidental--except for the fact that he had been hunting for Butch Cassidy's buried loot with a map he had gotten from his grandfather, a map believed to have been drawn by the leader of the Hole in the Wall gang himself. It isn't long before rumors circulate that Robert was murdered by his own cousins to get the map and find the treasure themselves. Despite there being no evidence of foul play, the gossip gains credibility when both Vicky and Father John are contacted by an anonymous Arapaho claiming to have witnessed Robert's killing. When one of Robert's cousins falls prey to another deadly accident, Vicky and Father John are convinced the victim is the witness who confided in them, and the hunt for the killer is on in earnest--before more die in search of Cassidy's cache"--